Polyester binder fibers and fibrous structures

CN122935629APending Publication Date: 2026-10-16KURARAY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202580020406.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-13
Filing Date
2025-03-06
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0048]The polyester adhesive fiber according to the present invention can bond the main fibers with high adhesive force, and can manufacture a fiber structure that is not only high in strength, but also has excellent air permeability and surface smoothness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935629A_ABST
    Figure CN122935629A_ABST
Patent Text Reader

Abstract

Provided is a polyester binder fiber capable of producing a fiber structure having high strength, excellent air permeability, and excellent smoothness of the surface. The polyester binder fiber has a tension at 50% elongation in a tension-elongation curve obtained in a tensile test of 0.33 to 0.50 cN / dtex.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application claims priority to Japanese Patent Application No. 2024-039196, filed on March 13, 2024, the entire contents of which are incorporated herein by reference. Technical Field

[0003] This application relates to polyester adhesive fibers and fiber structures comprising the polyester adhesive fibers. Background Technology

[0004] Considering its superior physical properties such as mechanical properties, heat resistance, water resistance, and dimensional stability, as well as its cost advantages, polyester fiber paper has been developed using polyester fibers as raw materials. It has been widely used in applications such as diapers, linings, wallpaper, insulating paper, partitions, and filters. In the production of polyester fiber paper, the polyester adhesive fibers used as raw materials have attracted considerable attention.

[0005] For example, Patent Document 1 (Japanese Patent Publication No. 49-8809) discloses a method for manufacturing polyester fiber paper. The method includes: preparing a paper material mainly composed of polyester fibers cut into fibers with a length of less than 15 mm and unstretched polyester fibers with a length of 6 to 0.1 mm; forming a paper web using a paper machine; and then bonding the paper by heating and pressing at a temperature below the secondary transformation point and melting point of the polyester fibers used.

[0006] Patent Document 2 (Japanese Patent Application Publication No. 57-82600) discloses a method for manufacturing polyester fiber paper, which includes: when manufacturing polyester fiber paper from stretched polyester staple fibers, incorporating at least 20% by weight of unstretched polyester staple fibers with a monofilament fineness of 1.3 denier or less into the polyester fiber paper. Patent Document 2 describes a method for manufacturing polyester fiber paper with excellent hand feel, texture, and strength.

[0007] Patent document 3 (Japanese Patent Application Publication No. 1-104823) discloses a polyester adhesive fiber, which is a polyester in which most of the repeating structural units are composed of polyethylene terephthalate, and has an limiting viscosity of 0.50 to 0.58, a monofilament fineness of 1.2 denier or less, and a birefringence Δn of 20 × 10⁻⁶. -3 The specific gravity is 1.35 or less. Patent document 3 describes a nonwoven fabric that can provide high nonwoven strength and a soft hand feel when using such polyester adhesive fibers.

[0008] Patent Document 4 (Japanese Patent Application Publication No. 2019-210566) discloses a polyester adhesive fiber, which is a fiber mainly composed of polyester resin, with a fineness of less than 0.5 dtex, a birefringence of 0.05 or less, a specific gravity of 1.37 or less, and a crystallization temperature of 80 to 150°C as determined by differential calorimetry. Patent Document 4 describes how polyester fiber paper with excellent density can be obtained by using such a polyester adhesive fiber.

[0009] Patent Document 5 (International Publication No. 2022 / 154072) discloses a polyester adhesive fiber in which ΔH, calculated from the difference between the heat of melting endotherm (ΔHm) and the heat of crystallization exotherm (ΔHc) obtained by differential scanning calorimetry, falls within a specific range. Furthermore, in the crystalline component ratio, the constrained amorphous component ratio, and the amorphous component ratio calculated by pulsed nuclear magnetic resonance (NMR) based on the free-induction decay signal of the spin-spin relaxation time, the ratio of the crystalline component ratio to the sum of the constrained amorphous component ratio and the amorphous component ratio falls within a specific range. Patent Document 5 describes such a polyester adhesive fiber as capable of bonding the main fibers with high adhesive strength, resulting in a high-strength fiber structure.

[0010] In addition, in recent years, polyester fiber paper has been increasingly used as a support for reverse osmosis membranes (RO membranes) used to obtain pure water from industrial wastewater and seawater. For example, Patent Document 6 (International Publication No. 2011 / 049231) discloses a semi-permeable membrane support, which is composed of a nonwoven fabric containing two or more main synthetic fibers with different fiber diameters and adhesive synthetic fibers, and the smoothness ratio of the coated surface to the uncoated surface of the semi-permeable membrane is 5.0:1.0 to 1.1:1.0.

[0011] Existing technical documents

[0012] Patent documents

[0013] Patent Document 1: Japanese Patent Publication No. 49-8809

[0014] Patent Document 2: Japanese Patent Application Publication No. 57-82600

[0015] Patent Document 3: Japanese Patent Application Publication No. 1-104823

[0016] Patent Document 4: Japanese Patent Application Publication No. 2019-210566

[0017] Patent Document 5: International Publication No. 2022 / 154072

[0018] Patent Document 6: International Publication No. 2011 / 049231 Summary of the Invention

[0019] The problem that the invention aims to solve

[0020] RO membranes are widely used as composite membranes made by coating polyamide resins onto a fibrous structure such as wet nonwoven fabric. In order to obtain high filtration performance and durability, a fibrous structure with high strength, excellent air permeability and excellent surface smoothness is required as the support.

[0021] However, in Patent Documents 1-5, although the adhesive strength was improved by controlling the properties of the polyester adhesive fiber, and the strength of fiber structures such as wet nonwoven fabrics was improved by using such polyester adhesive fiber, there was no record of the air permeability or surface smoothness of the obtained fiber structure.

[0022] Furthermore, in Patent Document 6, although the smoothness of the semipermeable membrane coating surface of the nonwoven fabric, which serves as a semipermeable membrane support, is improved by containing two or more main synthetic fibers and adhesive synthetic fibers with different fiber diameters, the influence of properties other than fiber morphology, such as fiber diameter and aspect ratio of the adhesive synthetic fibers, on the strength, air permeability, and surface smoothness of the nonwoven fabric is not evaluated.

[0023] Therefore, the object of the present invention is to provide polyester adhesive fibers capable of producing fiber structures with high strength, excellent breathability and excellent surface smoothness, and fiber structures formed by bonding main fibers with such polyester adhesive fibers.

[0024] Problem Solving Methods

[0025] In order to achieve the above objectives, the inventors of the present invention conducted in-depth research and found that when using polyester adhesive fibers with a tension range of 50% elongation at the tension-elongation curve obtained in the tensile test, it is possible to manufacture fiber structures with high strength, excellent air permeability, and excellent surface smoothness, thereby completing the present invention.

[0026] That is, the present invention can be constructed in the following ways.

[0027] [Method 1]

[0028] A polyester adhesive fiber, wherein the tension at 50% elongation of the tension-elongation curve obtained in a tensile test is 0.33~0.50 cN / dtex (preferably 0.35~0.48 cN / dtex, more preferably 0.37~0.46 cN / dtex).

[0029] [Method 2]

[0030] According to the polyester adhesive fiber of method 1, wherein,

[0031] The amount of antimony leached is less than 100 ppb (preferably less than 50 ppb, more preferably less than 30 ppb).

[0032] [Method 3]

[0033] The polyester adhesive fiber according to method 1 or 2 contains a titanium-based catalyst.

[0034] [Method 4]

[0035] The polyester adhesive fiber described according to any one of methods 1 to 3 is an unstretched fiber.

[0036] [Method 5]

[0037] A fiber structure comprising at least a polyester adhesive fiber and a main fiber as described in any one of embodiments 1 to 4, wherein the main fiber is formed by bonding the polyester adhesive fiber with the main fiber.

[0038] [Method 6]

[0039] The fiber structure described in Method 5 is a wet nonwoven fabric.

[0040] [Method 7]

[0041] According to the fiber structure described in Method 6, the arithmetic mean roughness Ra of its surface is less than 5.0 μm (preferably less than 4.8 μm, more preferably less than 4.0 μm).

[0042] [Method 8]

[0043] The fiber structure according to method 6 or 7, wherein...

[0044] The amount of antimony leached is less than 100 ppb (preferably less than 80 ppb, more preferably less than 50 ppb).

[0045] When used in this specification, unless explicitly stated otherwise, the singular form, “a,” “an,” and “the” all refer to the plural form containing “at least one.” When used in this specification, the terms “and / or,” “at least one,” and “more than one” include any and all combinations of the relevant listed items.

[0046] It should be noted that any combination of at least two constituent elements disclosed in the claims and / or specification is also included in this invention. In particular, any combination of two or more claims recited in the claims is also included in this invention.

[0047] The effects of the invention

[0048] The polyester adhesive fiber according to the present invention can bond the main fibers with high adhesive force, and can manufacture a fiber structure that is not only high in strength, but also has excellent air permeability and surface smoothness. Attached Figure Description

[0049] Figure 1 This is a tension elongation curve obtained from a tensile test of a polyester adhesive fiber.

[0050] Figure 2 This is a tension elongation curve obtained from a tensile test of polyester fiber.

[0051] Symbol Explanation

[0052] A···Elastic deformation region

[0053] B···Constant tension elongation region Detailed Implementation

[0054] (Polyester adhesive fiber)

[0055] The tension at 50% elongation of the tension-elongation curve obtained from tensile tests of polyester adhesive fibers is 0.33~0.50 cN / dtex. For the tension-elongation curve (SS curve) obtained from tensile tests of polyester adhesive fibers, the following is used... Figure 1 Please provide an explanation. Figure 1 The diagram shows the tension-elongation curve obtained from a tensile test of a polyester adhesive fiber. Tension is represented on the vertical axis as strength (cN / dtex), and elongation is represented on the horizontal axis as elongation (%). In the initial stage of elongation, as tension increases, there is essentially no elongation, and elastic deformation occurs (elastic deformation region A). When the tension reaches its maximum value (yield tension), necking occurs in the weaker portion of the fiber, followed by a decrease in tension. Then, necking propagates, exhibiting constant tension relative to elongation (constant tension elongation region B). Constant tension elongation region B continues until the unstretched portion disappears; the elongation at the end of constant tension elongation region B is called the natural stretch ratio. When the unstretched portion disappears, the tension increases again, and fracture occurs at the maximum stretch ratio.

[0056] Polyester adhesive fibers typically have a natural stretch ratio exceeding 50% elongation. Therefore, 50% elongation falls within the constant tension elongation region, exhibiting constant tension up to the natural stretch ratio. Thus, the tension at 50% elongation can be considered the tension at the natural stretch ratio. The tension at the natural stretch ratio is the tension required to orient the polymer chains in the unstretched portion of the polyester adhesive fiber; therefore, it can be considered to reflect the molecular mobility of the polymer chains. That is, the lower the tension at the natural stretch ratio, the weaker the intermolecular forces and other interactions, requiring only low tension to orient the polymer chains; therefore, the higher the molecular mobility of the polymer chains can be considered. Conversely, the higher the tension at the natural stretch ratio, the stronger the intermolecular interactions, requiring high tension to orient the polymer chains; therefore, the lower the molecular mobility of the polymer chains can be considered.

[0057] In this invention, by adjusting the tension at 50% elongation of the tension-elongation curve of the polyester adhesive fiber to a specific range, the molecular mobility of the polymer chains can be controlled, thereby controlling the adhesiveness and softening during hot pressing. Moreover, by using such polyester adhesive fibers, a fiber structure with high strength, excellent breathability, and surface smoothness can be obtained.

[0058] The tension at 50% elongation of the tension-elongation curve of the polyester binder fiber is preferably 0.35~0.48 cN / dtex, more preferably 0.37~0.46 cN / dtex. If the tension at 50% elongation is too low, for example during papermaking, the molecular mobility of the polymer chains is considered high, leading to fiber adhesion. This not only results in poor fiber dispersion during papermaking but also a tendency for fibers to adhere to the rolls during the drying and hot-pressing processes, resulting in paper with low strength, poor air permeability, and poor surface smoothness. On the other hand, if the tension at 50% elongation is too high, for example during papermaking, the molecular mobility of the polymer chains is considered low. Therefore, even after hot-pressing the paper, sufficient adhesion cannot be achieved, resulting in paper with low strength. In this specification, the tension at 50% elongation of the tension-elongation curve obtained from the tensile test of the polyester adhesive fiber is a value determined by the method described in the examples below.

[0059] Polyester adhesive fibers are composed of polyester resins. Polyester resins are condensation polymers of dicarboxylic acids and diols. Examples of dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid; and aliphatic dicarboxylic acids such as azelaic acid and sebacic acid. Examples of diols include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, polyethylene glycol, and polytetramethylene glycol; aromatic diols such as ethylene oxide adducts of bisphenol A or bisphenol S; and alicyclic diols such as cyclohexanediol.

[0060] Polyester resins constituting polyester adhesive fibers are preferably polyester resins with aromatic dicarboxylic acids as the main dicarboxylic acid component, such as polyethylene terephthalate, polybutylene terephthalate, and polycyclohexanediol terephthalate. These polyester resins can be copolymers of other diols, isophthalic acid, and other dicarboxylic acids as third components. Among these, polyethylene terephthalate is more preferred.

[0061] Polyester adhesive fibers may contain polymerization catalysts used in the synthesis of polyester resins. As a polymerization catalyst, any catalyst known as a polymerization catalyst for polyester resins can be used, as long as it does not impair the effects of this invention. Examples include compounds of titanium, germanium, aluminum, phosphorus, and antimony. From the viewpoint of adjusting the tension at 50% elongation of the tension elongation curve, a titanium catalyst is preferred. Conventionally, antimony catalysts have mostly been used as polymerization catalysts for polyester resins. However, titanium catalysts have higher catalytic activity than antimony catalysts, and it is known that side reactions such as the formation of diethylene glycol (DEG) components are prone to occur, for example, when using ethylene glycol as a diol for polymerization. By using a titanium catalyst to moderately generate side reaction components in the polyester resin, polymer chain entanglement and intermolecular forces between polymer chains occur. Therefore, although it also depends on the manufacturing method described later, it is possible to make the tension at 50% elongation of the tension elongation curve of the polyester adhesive fiber higher than that of polyester adhesive fibers composed of polyester resins using antimony catalysts.

[0062] Examples of titanium catalysts contained in polyester adhesive fibers include: tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-n-butyl titanate tetramer, tetra-tert-butyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, tetrabenzyl titanate, and other titanium alkoxides; titanium acetate, titanium propionate, titanium benzoate, titanium oxalate, and other titanium acylates; titanium acetylacetone, titanium tetraacetylacetone, titanium ethyl acetoacetate, titanium octanediol, titanium triethanolamine, titanium lactate, and other titanium chelates.

[0063] The antimony leaching content of polyester adhesive fibers can be 100 ppb or less, preferably 50 ppb or less, and more preferably 30 ppb or less. In recent years, concerns have been raised regarding the safety of antimony from an environmental perspective, particularly when polyester adhesive fibers are used as raw materials for the support of separation membranes such as filter membranes for drinking water and industrial water. There is a demand for significantly reduced antimony leaching. By using polyester adhesive fibers with reduced antimony leaching within a specific range as raw materials for fiber structures, the antimony leaching content of the resulting fiber structures can be significantly reduced, allowing for the use of environmentally friendly products. To significantly reduce antimony leaching, it is preferable to suppress the presence of antimony during manufacturing. For example, since the polymerization catalyst of the polyester resin used as the fiber raw material and the synthesis catalyst of the oiling component adhering to the fiber surface may contain antimony compounds, methods for excluding the use of such antimony compounds can be cited. In this specification, the antimony leaching content is a value measured by the method described in the examples described later.

[0064] The polyester adhesive fiber may contain thermoplastic resins such as polymethyl methacrylate, polystyrene, and polyetherimide, without impairing the effects of the present invention. From the viewpoint of preventing inhomogeneity that may occur due to resin blending, obtaining stable fibers, and obtaining fibers with high quality stability, the resin constituting the adhesive fiber is preferably a polyester resin alone. In addition, the polyester adhesive fiber may contain matting agents, heat stabilizers, ultraviolet absorbers, antistatic agents, end-capping agents, optical brighteners, etc., as needed.

[0065] The resin component constituting the polyester adhesive fiber may contain 95% by weight or more of polyester resin, preferably 98% by weight or more, and more preferably 99% by weight or more. Here, components (such as polymerization catalysts) that inevitably mix in during the synthesis process of the polyester resin, the manufacturing process of the polyester adhesive fiber, etc., can be considered as part of the polyester resin.

[0066] The intrinsic viscosity of the polyester adhesive fiber can be 0.40 to 1.1 dL / g. From the viewpoint of adjusting the tension at 50% elongation of the tension-elongation curve, it is preferably 0.45 to 0.80 dL / g, more preferably 0.50 to 0.70 dL / g, and even more preferably 0.60 to 0.70 dL / g. In this specification, the intrinsic viscosity is a value measured by the method described in the examples below.

[0067] The tension at 50% elongation of the polyester adhesive fiber's tension-elongation curve only needs to be within a specific range; it can be either unstretched or stretched fiber. Since the adhesive properties can be considered to be achieved by utilizing the molecular mobility of the amorphous portion, unstretched fiber is preferred from the viewpoint of further suppressing crystallization and increasing the component that exerts kinetic energy as an adhesive.

[0068] For polyester binder fibers, from the viewpoint of improving the processability of the fiber structure manufacturing process and the physical properties of the resulting fiber structure, the single fiber fineness can be 0.01 to 10 dtex. For example, in the manufacture of wet nonwoven fabrics (e.g., a method of dispersing fibers in water for papermaking), no mechanical entanglement of the fibers occurs, and compared with the manufacture of dry nonwoven fabrics, thread breakage is less likely to occur. Therefore, the single fiber fineness of the polyester binder fibers used in the manufacture of wet nonwoven fabrics is preferably 0.01 to 10 dtex, more preferably 0.05 to 5.0 dtex, and even more preferably 0.1 to 3.0 dtex.

[0069] The polyester binder fiber can be a short fiber, for example, with a fiber length of 0.5 to 50 mm, depending on the type of fiber structure. In the case of manufacturing paper, which is an example of wet nonwoven fabric, from the viewpoint of improving the throughput of the manufacturing process and the physical properties such as the strength of the obtained paper, the fiber length can be 0.5 to 15 mm, preferably 0.8 to 10 mm, and more preferably 1 to 7 mm.

[0070] Polyester adhesive fibers can be non-composite fibers. In this specification, non-composite fiber refers to a fiber that is not a composite fiber, while composite fiber refers to a fiber obtained through composite spinning that has a continuous composite cross-section along the fiber axis. Non-composite fibers include mixed spun fibers obtained by mixing the other components mentioned above and then spinning. Furthermore, polyester adhesive fibers can be solid fibers.

[0071] The method for manufacturing polyester adhesive fibers includes a spinning step of melt spinning a resin material containing polyester resin. In the spinning step, molten resin is ejected from the nozzle orifice to form a filament, and fibers can be obtained by drawing the filament.

[0072] By adjusting the type of polymerization catalyst for polyester resin, the viscosity of the chips (intrinsic viscosity) and other raw material resin conditions, as well as the spinning conditions in the spinning process corresponding to the raw material resin conditions, such as the spinning head temperature, nozzle surface temperature, diameter, ejection rate, traction speed, cooling air temperature and wind speed, the tension of the obtained polyester adhesive fiber at 50% elongation can be adjusted.

[0073] For example, regarding the raw material resin, as described above, from the viewpoint of adjusting the tension at 50% elongation of the tension elongation curve to a high level, it is preferable to use a titanium-based catalyst as the polymerization catalyst for the polyester resin. Furthermore, since increasing the chip viscosity of the polyester resin increases the entanglement of the polymer chains and the intermolecular interactions between the polymer chains, it tends to increase the tension at 50% elongation of the tension elongation curve. For example, from the viewpoint of adjusting spinnability and the tension at 50% elongation of the tension elongation curve, the chip viscosity of the polyester resin can be 0.40~1.1 dL / g, preferably 0.45~0.80 dL / g, more preferably 0.50~0.70 dL / g, and even more preferably 0.60~0.70 dL / g. In this specification, the chip viscosity (intrinsic viscosity) is a value measured by the method described in the examples described later.

[0074] Spinning conditions vary depending on factors such as the polymerization catalyst of the polyester resin, the chip viscosity (intrinsic viscosity), the melting point of the raw resin, and the desired fineness. For example, by controlling the cooling air velocity within an appropriate range, the tension at 50% elongation of the tension-elongation curve can be adjusted. The cooling air velocity is preferably 0.5 to 1.5 m / s, more preferably 0.8 to 1.2 m / s. Furthermore, by lowering the cooling air temperature, the tension at 50% elongation of the tension-elongation curve can be adjusted to a higher level. The cooling air temperature can be below 40°C, preferably 15 to 40°C.

[0075] In the manufacturing method of polyester adhesive fibers, from the viewpoint of productivity and tension at 50% elongation of the tension elongation curve, the spinning speed (traction speed) can be 500~3000m / min, preferably 600~2000m / min, and more preferably 800~1500m / min.

[0076] In the manufacturing method of polyester adhesive fibers, a stretching process can be included, whereby the tension at 50% elongation of the tension-elongation curve is adjusted to a specific range, as long as the polyester adhesive fiber can be obtained. To maintain or adjust the tension at 50% elongation of the tension-elongation curve to a specific range and reduce the fineness of individual fibers, a method of superdrawing can be used. Superdrawing is a method of stretching the obtained undrawn fibers at a temperature higher than their glass transition temperature, which can achieve finer fineness while maintaining the molecular orientation of the undrawn fibers.

[0077] In superstretching, from the viewpoint of adjusting the tension at 50% elongation of the tension-elongation curve, it is preferable to adjust stretching conditions such as temperature and stretch ratio. For example, the superstretching temperature depends on the type of polyester resin, and can be, for example, 80~120°C, preferably 85~115°C, and more preferably 90~110°C. Furthermore, the superstretching stretch ratio can be 1.1~5 times, preferably 1.5~3 times, and more preferably 1.8~2.5 times.

[0078] (Main fiber)

[0079] Polyester binder fibers can be used to bond the main fibers to create a fiber structure. In this embodiment, the fiber structure typically contains the main fibers along with the polyester binder fibers. Various fibers can be used as the main fibers, as long as they do not impair the effects of the invention. For example, in the case of manufacturing wet nonwoven fabrics, polyester fibers, pulp, other papermaking main fibers, etc., can be included. From the viewpoint of improving the surface smoothness of the resulting fiber structure, polyester fibers are preferred.

[0080] The preferred tension for polyester fibers at 5% elongation in the tensile elongation curve obtained in the tensile test is 1.20~2.00 cN / dtex. Figure 2 The diagram shows the tension-elongation curves of polyester fibers obtained in a tensile test. Tension is represented on the vertical axis as strength (cN / dtex), and elongation is represented on the horizontal axis as elongation (%). Figure 2 As shown, the tensile elongation curve of polyester fiber obtained in the tensile test is different from that of polyester adhesive fiber obtained in the tensile test. Polyester fiber is a high elastic fiber, so the increase in tension relative to elongation is large and the breaking elongation is small.

[0081] For polyester fibers, focusing on the tension at 5% elongation, which falls within the elastic deformation region of the initial elongation stage, allows for control of the molecular mobility of the polymer chains by adjusting the tension at 5% elongation within a specific range of the polyester fiber's tension-elongation curve. This, in turn, enables control over dispersion and deformability during hot pressing. Furthermore, using such polyester fibers as the main fiber results in a fiber structure with superior surface smoothness.

[0082] The tension at 5% elongation of the tension-elongation curve of the polyester fiber is more preferably 1.30~1.90 cN / dtex, and even more preferably 1.50~1.80 cN / dtex. When the tension at 5% elongation of the tension-elongation curve is above or above the aforementioned lower limit, for example, when supplied for papermaking, it can be considered that the molecular mobility of the polymer chains is not too high. Therefore, not only can the fiber dispersion during papermaking be improved by suppressing fiber adhesion, but also, during the drying and hot pressing processes of the paper after papermaking, there is a tendency for the fibers to not easily adhere to the rollers, resulting in excellent surface smoothness of the obtained paper. On the other hand, when the tension at 5% elongation of the tension-elongation curve is below or above the aforementioned upper limit, for example, when supplied for papermaking, it can be considered that the molecular mobility of the polymer chains is not too low. When the paper after papermaking is hot-pressed, it can be sufficiently deformed, resulting in excellent surface smoothness of the obtained paper. In this specification, the tension at 5% elongation of the tension-elongation curve obtained by the polyester fiber in the tensile test is a value measured by the method described in the examples described later.

[0083] The tension at 5% elongation on the tension-elongation curve of polyester fiber only needs to be within a specific range. When used as the main fiber of the fiber structure, high tensile strength is required, therefore, stretched fibers are preferred. Through stretching, the amorphous component crystallizes, resulting in polyester fibers for example, in which no crystallization peak is observed in the DSC curve of the heating process obtained by differential scanning calorimetry (DSC). In this specification, if the crystallization peak (exothermic peak) is broad and cannot be clearly identified as a peak, it can be determined that no crystallization peak was observed.

[0084] Polyester fibers are composed of polyester resins, and the aforementioned polyester resins can be used. The resin component constituting the polyester fiber may contain 95% by weight or more of polyester resin, preferably 98% by weight or more, and more preferably 99% by weight or more. Here, components inevitably mixed in during the synthesis process of the polyester resin, the manufacturing process of the polyester fiber, etc. (e.g., polymerization catalysts) can also be considered as part of the polyester resin. From the viewpoint of obtaining a high-strength fiber structure by improving adhesive strength, the polyester fiber as the main fiber may contain the same polyester resin as the polyester resin constituting the polyester adhesive fiber as its main component. Furthermore, the polyester fiber may contain a polymerization catalyst used in the synthesis of the polyester resin; the aforementioned polymerization catalysts can be used as polymerization catalysts. From the viewpoint of adjusting the tension at 5% elongation of the tension elongation curve, it is preferable to include a titanium-based catalyst. Because titanium catalysts have higher catalytic activity than antimony catalysts, by moderately generating by-reaction components in polyester resins, even if crystallization is carried out by stretching, the crystallinity is low. Therefore, although it also depends on the manufacturing method described later, the tension of polyester fibers at 5% elongation of the tension elongation curve can be lower than that of polyester fibers made from polyester resins using antimony catalysts.

[0085] From an environmental perspective, the antimony leaching amount of polyester fibers can be below 100 ppb, preferably below 50 ppb, and more preferably below 30 ppb. Not only are the polyester adhesive fibers with reduced antimony leaching within a specific range, but the polyester fibers as the main fibers also have reduced antimony leaching within a specific range, thereby achieving a higher degree of reduction in the antimony leaching amount of the resulting fiber structure.

[0086] From the viewpoint of improving the throughput of the manufacturing process of the fiber structure and the physical properties of the resulting fiber structure, the single fiber fineness of polyester fiber can be 0.01 to 10 dtex. For example, the single fiber fineness of polyester fiber used in the manufacture of wet nonwoven fabric is preferably 0.01 to 10 dtex, more preferably 0.05 to 5.0 dtex, and even more preferably 0.1 to 3.0 dtex.

[0087] Polyester fibers can be short fibers, depending on the type of fiber structure, for example, the fiber length can be 0.5 to 50 mm. In the case of manufacturing paper as an example of wet nonwoven fabric, from the viewpoint of improving the throughput of the manufacturing process and the physical properties such as the strength of the obtained paper, the length can be 0.5 to 15 mm, preferably 0.8 to 10 mm, and more preferably 1 to 7 mm.

[0088] Polyester fiber can be a non-composite fiber. Additionally, polyester fiber can be a solid fiber.

[0089] The method for manufacturing polyester fibers can include a stretching step of stretching the aforementioned polyester binder fibers. By stretching polyester binder fibers with a tension within a specific range at 50% elongation of the tension-elongation curve to crystallize them, the tension at 5% elongation of the tension-elongation curve can be adjusted, thereby manufacturing the aforementioned polyester fibers. Unstretched fibers obtained through the spinning step in the aforementioned method for manufacturing polyester binder fibers can be temporarily wound up, then unwound and stretched, or they can be stretched directly connected to the spinning process without being wound up after spinning. Regardless of whether the stretching is performed after temporary winding or directly connected, the stretching step can be performed after the aforementioned overstretching.

[0090] The stretching method can employ known methods, such as necking stretching at a temperature below the glass transition temperature of the unstretched fiber, or stretching between rollers with varying rotational speeds. Furthermore, from the viewpoint of improving fineness and mechanical strength, a stretching method involving two or more stages is preferred. Additionally, depending on the type of polyester resin, stretching can also be performed in a warm water bath at 65–98°C. In the case of two-stage stretching, for example, the first stage can be performed at a relatively low temperature of 65–80°C, and the second stage at a relatively high temperature of 80–98°C. The total stretching ratio in the stretching process can be 1.1–5 times, preferably 1.5–3 times, and more preferably 1.8–2.5 times.

[0091] Alternatively, the polyester fibers can be heat-shrinked in a warm water bath between the rollers during the stretching process, or they can be heat-fixed on the hot rollers after the stretching process. Furthermore, from the viewpoint of using them as the main fiber of wet nonwoven fabrics, the resulting polyester fibers can be cut to the desired length.

[0092] (Fiber structure)

[0093] Polyester binder fibers can be used to bond host fibers to create fiber structures. The fiber structure only needs to contain at least polyester binder fibers and host fibers; its form is not limited and can include various fabrics such as nonwovens, textiles, and woven goods, with nonwovens being preferred.

[0094] From the viewpoint of the physical properties of the fiber structure, the weight ratio (main fiber / polyester adhesive fiber) of the main fiber to the polyester adhesive fiber constituting the fiber structure (e.g., wet nonwoven fabric) can be 95 / 5 to 5 / 95, preferably 80 / 20 to 20 / 80, more preferably 75 / 25 to 25 / 75, further preferably 70 / 30 to 30 / 70, and even more preferably 70 / 30 to 50 / 50.

[0095] The weight per unit area and thickness of fiber structures can be adjusted according to their type and application; for example, the weight per unit area can be 40~120g / m². 2 The preferred value is 50~100g / m 2 More preferably, it can be 60~90g / m 2 Additionally, the thickness can be 0.01~2mm, preferably 0.03~1mm, and more preferably 0.05~0.5mm. It should be noted that the weight per unit area and thickness are values ​​measured using the methods described in the embodiments below.

[0096] The fiber structure is preferably a wet nonwoven fabric, and more preferably paper. The wet nonwoven fabric obtained using polyester binder fibers has high strength. The tensile strength (e.g., paper strength) of the wet nonwoven fabric varies depending on the thickness. For example, with a thickness of approximately 0.1 to 0.2 mm, it can be 8.0 kg / 15 mm or more, preferably 9.0 kg / 15 mm or more, more preferably 9.5 kg / 15 mm or more, and the upper limit is not particularly limited, but can be approximately 30 kg / 15 mm. It should be noted that the tensile strength of the wet nonwoven fabric is a value measured by the method described in the examples described later.

[0097] In addition, wet nonwoven fabrics made using polyester binder fibers exhibit excellent air permeability. The air permeability of wet nonwoven fabrics varies depending on factors such as thickness and weight per unit area. For example, at a thickness of approximately 0.1~0.2 mm, it can achieve an air permeability of 1.8 cm. 3 / cm 2 / s or higher, preferably 2.0cm 3 / cm 2 / s or higher. There is no specific upper limit; it can be 3.0cm. 3 / cm 2 Approximately / s. It should be noted that the air permeability is a value measured using the method described in the examples described later.

[0098] From an environmental perspective, the antimony leaching amount of wet nonwoven fabric can be below 100 ppb, preferably below 80 ppb, and more preferably below 50 ppb. Wet nonwoven fabrics with further significantly reduced antimony leaching can be suitable for use as supports for RO membranes, liquid filters, etc.

[0099] The surface smoothness of wet nonwoven fabrics obtained using polyester binder fibers is excellent. In this specification, the arithmetic mean roughness Ra, as described in JIS B 0601:2001, is used as an indicator of surface smoothness. The arithmetic mean roughness Ra is an indicator of roughness in the height direction; in a roughness curve over a reference length, the unevenness of that interval is represented by the average of the absolute values ​​of the deviations from the mean line to the roughness curve. The arithmetic mean roughness Ra of the wet nonwoven fabric surface is preferably less than 5.0 μm, more preferably less than 4.8 μm, and even more preferably less than 4.0 μm. Its lower limit is not particularly limited and can be 1.0 μm or more. By setting the arithmetic mean roughness Ra to the above range, even when a separation membrane is coated, a uniform separation membrane can be obtained, resulting in RO membranes with high filtration performance and durability. In this specification, the arithmetic mean roughness Ra is a value measured by the method described in the examples described later.

[0100] Fiber structures can be manufactured using polyester binder fibers through known or conventional methods. For example, dry nonwoven fabrics can be manufactured by forming a web without the use of water using a carding machine or similar equipment, and then heating the web to allow the polyester binder fibers to bond the main fibers together.

[0101] In addition, wet nonwoven fabrics can be produced by forming a web using water in the manufacturing process, drying the web as needed, and then heating the web to bond the fibers together with adhesive fibers. Specific methods for forming a web using water in the manufacturing process include: papermaking, where fibers are dispersed in water to create a paper-like web; or water-based methods where the web is formed without using water and then water is used to bind the fibers together.

[0102] When manufacturing paper as a wet nonwoven fabric, the polyester binder fibers used in papermaking can be cut to a cut length of 0.5 to 15 mm, preferably 0.8 to 10 mm, and more preferably 1 to 7 mm, after spinning before being fed into the papermaking machine. If the cut length is too short, there is a tendency for insufficient bonding force in the bonding of the main fibers; if the cut length is too long, the fibers tend to entangle with each other, resulting in poor dispersibility in water.

[0103] As a papermaking method, well-known methods can be used, such as the cylinder papermaking method, the short-wire papermaking method, etc.

[0104] After forming a paper-like web, the web can be dried using known apparatus. After drying, the web can be pressurized at high temperature to obtain paper. In the pressurization process, the polyester binder fibers are heated to a temperature below their melting point, causing them to deform and strongly entangle with the main fibers. After cooling, the fibers are cured while still deformed, forming paper firmly bonded to the main fibers.

[0105] Specifically, the temperature used in the pressurization process can be, for example, 150~250°C, preferably 160~245°C, and more preferably 180~240°C. The duration of the high-temperature treatment in the pressurization process can be less than 15 minutes, preferably less than 12 minutes, and more preferably less than 10 minutes.

[0106] In the pressurization process, from a production standpoint, it is preferable to continuously perform hot pressing between the pressure rollers. For example, when hot pressing is performed between steel rollers, the hot-pressed paper may sometimes adhere to the steel rollers after hot pressing due to the adhesive properties of the adhesive fibers. In continuous production, the hot-pressed paper is continuously peeled off from the steel rollers while being wound up, but if the load required for peeling is large, the hot-pressed paper may sometimes break. In addition, even after peeling, the surface of the resulting paper may sometimes be rough, resulting in hot-pressed paper with poor surface smoothness. By using polyester adhesive fibers, adhesion to the rollers can be suppressed. In this specification, as a method for evaluating adhesion to the steel rollers, the rollers are temporarily stopped, a spring scale is fixed to the adhered paper, and the rollers are rotated at 1 m / min to peel off the paper. The load at this time is used as an indicator. The paper's roller adhesion varies depending on the paper thickness, roller temperature, etc. For example, for a thickness of about 0.1 to 0.2 mm, it can be 220 gf or less, preferably 200 gf or less.

[0107] Example

[0108] The present invention will now be described in further detail based on embodiments, but the invention is not limited thereto. It should be noted that in the following embodiments and comparative examples, various physical properties were measured using the methods described below.

[0109] (Slice viscosity (intrinsic viscosity))

[0110] The intrinsic viscosity (dL / g) of the resin before spinning and the intrinsic viscosity (dL / g) of the resulting fiber were measured using an automatic viscosity measuring device (SS-600-L1 type, Shibayama Scientific Instruments Co., Ltd.). A phenol / tetrachloroethane (1 / 1 volume ratio) mixture was used as the solvent for the measurement at 30°C.

[0111] (Single fiber fineness)

[0112] 300 single fibers were extracted from the uncut fiber bundle, aligned with tweezers, and cut into 30mm lengths. After being subjected to temperature and humidity conditioning (20±2℃, 65±4%RH) for more than 3 hours, the weight of the 300 single fibers was measured using an electronic balance, and the apparent fineness was calculated. This apparent fineness was divided by the number of single fibers (300), and the quotient was taken as the single fiber fineness (dtex).

[0113] (Tension test)

[0114] Single fibers were individually extracted from the uncut filament bundle and adhered to a continuous paper sheet, with the test length set at 20 mm. Tensile tests were conducted using an automatic short fiber tensile testing device (A&D Corporation, "AMS-D") at a test speed of 20 mm / min, according to section 8.7.1 of JIS L 1015 "Test Methods for Short Fibers of Chemical Fibers". Tensile tests were performed on one sample 30 times. For polyester adhesive fibers, the tension (cN / dtex) at 50% elongation was obtained from the tension-elongation curve; for polyester fibers, the tension (cN / dtex) at 5% elongation was obtained from the tension-elongation curve. The average value of the 30 tests was calculated. Additionally, the average value of the tension and elongation at break in the tension-elongation curve of the polyester adhesive fiber was calculated as the strength (cN / dtex) and elongation (%).

[0115] (Antimony content)

[0116] Regarding the resin before spinning, the resin sample was microwave decomposed using a microwave decomposition device (ETHOS1, Milestone General), and the antimony content was determined using an ICP-MS analysis device (Agilent 7900, Agilent Technology).

[0117] Regarding the obtained fibers, approximately 2g of fiber sample was rinsed with ultrapure water for 3 minutes to clean the fiber surface. After rinsing, vacuum drying was performed at 80°C to remove moisture. The dried fiber sample was then subjected to microwave decomposition using the same microwave decomposition apparatus as the resin sample described above, and the antimony content was determined using an ICP-MS analysis device.

[0118] (Antimony leaching amount)

[0119] 1.7 g of fiber or paper was immersed in 200 mL of ultrapure water and allowed to stand at 25 ± 3 °C for 24 hours. Then, the extract was stirred while still containing the fiber or paper, filtered, and the filtrate was used as a sample (50 mL). The amount of antimony in the filtrate was determined using an ICP-MS analyzer, and the amount of antimony dissolved was calculated.

[0120] (Weight per unit area)

[0121] The weight per unit area (g / m²) of the paper was determined according to the JIS P 8124 test method. 2 ).

[0122] (thickness)

[0123] The thickness (mm) of the paper was determined according to the JIS P 8118 test method.

[0124] (Roller adhesion)

[0125] A spring scale was attached to the paper that was glued to the steel roller during hot pressing, and the steel roller was rotated at a speed of 1 m / min. The load (gf) when the paper was peeled off was measured.

[0126] (Paper strength (tensile strength))

[0127] The paper strength (tensile strength) (kg / 15mm) was determined according to the JIS P 8113 test method.

[0128] (Breathability)

[0129] According to section 8.26 of JIS L 1096 "Test Methods for Textiles and Woven Fabrics", the air permeability (cm²) was determined using the Frazier method. 3 / cm 2 / s).

[0130] (Arithmetic mean roughness Ra)

[0131] A paper sample (50mm × 50mm) was horizontally fixed to a fixing plate (approximately 15cm × approximately 20cm, 3mm thick vinyl chloride plate). Using a surface roughness tester (Mitutoyo "SURTEST SJ-410"), after setting up the drive unit and detector and determining their vertical positions, the evaluation length in the MD direction (mechanical direction) of the hot pressing was set to 4mm. The arithmetic mean roughness was measured five times on both the front and back sides at different locations, and the average value was calculated as the arithmetic mean roughness (Ra). A needle with a cone angle of 60 degrees and a front-end radius of curvature of 2μm was used in the measurement.

[0132] [Example 1]

[0133] Polyethylene terephthalate resin (manufactured by Shinko Synthetic Fiber Co., Ltd., "SHINPET") polymerized with a titanium catalyst and having a chip viscosity (intrinsic viscosity) of 0.643 dL / g was fed into a melt extruder for melting. The resin was then extruded from a spinning nozzle with a diameter of 0.14 mm and 1880 orifices at a rate of 354 g / min for spinning (spinneret temperature: 300°C, nozzle surface temperature: 280°C). The resin was cooled under the nozzle with a cooling air velocity of 1.0 m / s and a cooling air temperature of 30°C, and then drawn at a speed of 1300 m / min to obtain polyester adhesive fibers with the properties shown in Table 1.

[0134] [Example 2]

[0135] The ejection rate was set to 326 g / min, the cooling air velocity under the spinning nozzle was set to 1.1 m / s, and the traction speed was set to 1200 m / min. Otherwise, the spinning precursor was obtained in the same manner as in Example 1. The obtained spinning precursor was super-stretched in boiling water at 100°C at a stretch ratio of 2 to obtain polyester adhesive fibers with the properties shown in Table 1.

[0136] [Comparative Example 1]

[0137] Polyethylene terephthalate resin (manufactured by Tainan Textile Co., Ltd., "NANLON") with a chip viscosity (intrinsic viscosity) of 0.638 dL / g and polymerized with an antimony catalyst was used. Otherwise, polyester adhesive fibers with the properties shown in Table 1 were obtained in the same manner as in Example 1.

[0138] [Comparative Example 2]

[0139] Polyethylene terephthalate resin (NANLON, manufactured by Tainan Textile Co., Ltd.) with an intrinsic viscosity of 0.576 dL / g and polymerized with an antimony catalyst was used. The spray rate was set to 326 g / min, the cooling air velocity under the spinning nozzle was set to 1.1 m / s, and the traction speed was set to 1200 m / min. Otherwise, polyester adhesive fibers with the properties shown in Table 1 were obtained in the same manner as in Example 1.

[0140] [Comparative Example 3]

[0141] Polyethylene terephthalate resin (manufactured by Tainan Textile Co., Ltd., "NANLON") with a chip viscosity (intrinsic viscosity) of 0.587 dL / g and polymerized with an antimony catalyst was used. The cooling air velocity under the spinning nozzle was set to 1.7 m / s. Otherwise, polyester adhesive fibers with the properties shown in Table 1 were obtained in the same manner as in Example 1.

[0142]

[0143] [Reference Example 1]

[0144] Polyester fiber (Kuraray Co., Ltd. "EP-043", single fiber fineness: 0.6 dtex, cut length: 5 mm, using antimony catalyst) was used as the main fiber. The tensile strength of this polyester fiber at 5% elongation was 2.15 cN / dtex, and the antimony leaching amount was 4610 ppb.

[0145] [Reference Example 2]

[0146] The polyester adhesive fiber (unstretched fiber) obtained in Example 1 was subjected to a two-stage stretching process at a total stretch ratio of 3.57 times in warm water baths set at 70°C and 85°C, respectively. Then, it was heat-fixed using hot rollers set at 175°C and 185°C, respectively, to obtain polyester fiber (stretched fiber). The obtained polyester fiber had a single fiber fineness of 0.6 dtex, a tensile strength at 5% elongation of 1.76 cN / dtex, and an antimony leaching amount of 50 ppb.

[0147] [Example 3]

[0148] Polyester binder fibers obtained in Example 1, cut to 5 mm, and polyester fibers (main fibers) from Reference Example 1 were added to a water bath in a debonding machine (manufactured by Tester Sangyo) at a weight ratio of main fiber / binder fiber = 60 / 40. After the fibers were separated in water at 3000 rpm for 1 minute, papermaking was performed using a Tappi paper machine (manufactured by Kumagai Riki Kogyo Co., Ltd.). Then, a press (manufactured by Kumagai Riki Kogyo Co., Ltd.) was used at a pressure of 3.5 kg / cm². 2 After applying pressure for 30 seconds and adjusting the moisture content, the material was dried for 1 minute at 110°C using a rotary dryer (manufactured by Kumagai Riki Kogyo Co., Ltd.) to obtain a paper-like wet nonwoven fabric. The obtained paper-like wet nonwoven fabric was then passed through hot press rollers (200°C, gap: 0.1 mm) made of steel on both the top and bottom sides at a pressure of 12 kg / cm and a speed of 3 m / min to obtain paper. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0149] [Example 4]

[0150] The polyester fibers obtained in Reference Example 2 were cut into 5 mm pieces as the main fibers, and otherwise, paper was obtained in the same manner as in Example 3. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0151] [Example 5]

[0152] The polyester adhesive fiber obtained in Example 2 was used as the adhesive fiber, and otherwise, paper was obtained in the same manner as in Example 3. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0153] [Comparative Example 4]

[0154] The polyester adhesive fiber obtained in Comparative Example 1 was used as the adhesive fiber, and otherwise, paper was obtained in the same manner as in Example 3. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0155] [Comparative Example 5]

[0156] The polyester adhesive fiber obtained in Comparative Example 2 was used as the adhesive fiber, and otherwise, paper was obtained in the same manner as in Example 3. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0157] [Comparative Example 6]

[0158] The polyester adhesive fiber obtained in Comparative Example 3 was used as the adhesive fiber, and otherwise, paper was obtained in the same manner as in Example 3. The results of evaluating the physical properties of the obtained paper are shown in Table 2.

[0159]

[0160] As shown in Table 2, the papers of Examples 3-5 obtained using polyester binder fibers from Examples 1 and 2, with tension within a specific range at 50% elongation, exhibit high tensile strength, excellent air permeability, and superior surface smoothness. Particularly in Example 4, since the polyester main fiber used was the polyester fiber from Reference Example 2, with tension within a specific range at 5% elongation, the arithmetic mean roughness Ra was lower than that of Examples 3 and 5, resulting in exceptionally superior surface smoothness. Furthermore, in Example 4, the polyester main fiber also used polyester fibers made from polyester resins utilizing titanium-based catalysts; therefore, the amount of antimony leached from the resulting hot-pressed paper was extremely low.

[0161] On the other hand, in Comparative Example 4, since polyester adhesive fibers with tension outside a specific range at 50% elongation were used, the resulting paper not only had low tensile strength, but also had an arithmetic mean roughness Ra higher than that of Examples 3-5, and poor surface smoothness.

[0162] Furthermore, in Comparative Examples 5 and 6, because polyester binder fibers with tension outside a specific range at 50% elongation were used, the resulting paper had lower air permeability than Examples 3-5, higher arithmetic mean roughness Ra than Examples 3-5, and poorer air permeability and surface smoothness. Additionally, the high load in roll adhesion (up to 250 gf) can be considered not only to worsen processability but also to contribute to the poor surface smoothness.

[0163] Industrial applicability

[0164] Polyester binder fibers are useful as binder fibers in fiber structures that contain main fibers (especially polyester fibers). Furthermore, wet nonwoven fabrics obtained using such polyester binder fibers are particularly useful as filter materials and supports in applications subject to high water pressure, such as RO membranes and liquid filters.

[0165] As described above, preferred embodiments of the present invention have been explained, but various additions, modifications or deletions may be made without departing from the spirit of the present invention, and these are also included within the scope of the present invention.

Claims

1. A polyester adhesive fiber, wherein the tension at 50% elongation of the tension-elongation curve obtained in a tensile test is 0.33~0.50 cN / dtex.

2. The polyester adhesive fiber according to claim 1, wherein, The antimony leaching amount is below 100 ppb.

3. The polyester adhesive fiber according to claim 1 or 2, wherein it comprises a titanium-based catalyst.

4. The polyester adhesive fiber according to claim 1 or 2, wherein it is an unstretched fiber.

5. A fiber structure comprising at least the polyester adhesive fiber and the body fiber as described in claim 1 or 2, wherein the polyester adhesive fiber bonds the body fiber together.

6. The fiber structure according to claim 5, wherein it is a wet nonwoven fabric.

7. The fiber structure according to claim 6, wherein the arithmetic mean roughness Ra of its surface is less than 5.0 μm.

8. The fiber structure according to claim 6, wherein, The antimony leaching amount is below 100 ppb.

Citation Information

Patent Citations

  • JP1974008809B1

  • Production of polyester fiber paper

    JP1982082600A

  • Polyester binder yarn

    JP1989104823A

  • Polyester-based binder fiber

    JP2019210566A

  • Composite fiber cord for reinforcing rubber and manufacturing method thereof

    JP2024039196A